The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3390/molecules17032542
|View full text |Cite
|
Sign up to set email alerts
|

The Artemisia L. Genus: A Review of Bioactive Essential Oils

Abstract: Numerous members of the Anthemideae tribe are important as cut flowers and ornamental crops, as well as being medicinal and aromatic plants, many of which produce essential oils used in folk and modern medicine and in the cosmetics and pharmaceutical industry. Essential oils generally have a broad spectrum of bioactivity, owing to the presence of several active ingredients that work through various modes of action. Due to their mode of extraction, mostly by distillation from aromatic plants, they contain a var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
403
0
9

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 484 publications
(415 citation statements)
references
References 67 publications
3
403
0
9
Order By: Relevance
“…The bioactive compounds isolated from A. nilagirica such as flavonoids, sesquiterpene lactones have been reported to have antimicrobial, cytotoxic, and insecticidal properties Paneerselvam et al 2012). Essential oils borneol, caryophyllene oxide, camphor, 2-hexane-1-ol, b-thujone, thujanol, myrtenol and lynalyl acetate, a-pinene, b-pinene, limonene, linalool, cgurijunene, germacrane D and farnesol have been isolated from Artemisia nilagirica (Haider et al 2010;Sati et al 2013) and majority of these essential oil possess medicinal and pharmacological properties (Abad et al 2012). The plant is also used traditionally in the preparation of insecticide (Bhattacharjee 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The bioactive compounds isolated from A. nilagirica such as flavonoids, sesquiterpene lactones have been reported to have antimicrobial, cytotoxic, and insecticidal properties Paneerselvam et al 2012). Essential oils borneol, caryophyllene oxide, camphor, 2-hexane-1-ol, b-thujone, thujanol, myrtenol and lynalyl acetate, a-pinene, b-pinene, limonene, linalool, cgurijunene, germacrane D and farnesol have been isolated from Artemisia nilagirica (Haider et al 2010;Sati et al 2013) and majority of these essential oil possess medicinal and pharmacological properties (Abad et al 2012). The plant is also used traditionally in the preparation of insecticide (Bhattacharjee 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Artemisia of the Asteraceae family includes over 500 species, of which A. gmelinii and A. capillaris, both called 'Injin' have long been used as a folk medicine in Korea (Abad et al 2012;Wang et al 2012). Previous studies have reported that A. gmelinii and A. capillaris contain useful metabolites with various pharmacological effects such as anti-infective and anti-oxidant activity and hepatoprotective and antifibrotic effects (K€ oncz€ ol et al 2012;Wang et al 2012).…”
Section: Main Textmentioning
confidence: 99%
“…Complete chloroplast genome sequence of Artemisia fukudo Makino (Asteraceae) The Artemisia genus belongs to the Asteraceae family and is a native to Europe, North Africa, and Asia, including Korea (Abad et al 2012). In Korea, about 20 Artemisia species were found and have been used as ingredients for food and as medicinal herbs for a long time (Kim et al 2007).…”
Section: Mitogenome Announcementmentioning
confidence: 99%